Designing a Device that Uses Sensor to Measure Blood Sugar Levels - Muhammed, Hussein Abeer; Saleh, Dhari Abdul - Sattar; Abbas, Ali Saady; Al-Deen, Abdullah Waeel Wasam (American Journal of Bioscience and Clinical Integrity, 2025)
Diabetes is the most commonly occurring diseases around the world; approximately 415 million people among the 8 billion population of the world suffer from diabetes. Diabetes is caused due to increase in the blood sugar concentration which may affect the heart, blood vessels, kidney and nerves, etc. The monitoring of blood sugar level is very important in case of diabetic patients, since it is necessary to keep the blood sugar level in limit. Hence, it is necessary to regularly monitor the blood glucose level of the diabetic patients. Currently, the measurement of the blood sugar level is done only by pricking the finger which is a painful process and may cause infections, the patients get suffer from physical pains and it has a higher risk of infection. The non-invasive procedure does not involve any pricking of the finger; hence there is no pain or chance of infections. Therefore, we propose a non-invasive method using infrared sensor for transmission and receiving of rays to and from fingertip for real-time monitoring of the sugar level. Because to determine blood sugar levels is only done by put finger index on the sensor, the results will display after 30 seconds, and does not hurt the fingers. So that this tool can be used by all groups, both medical and non-medical personnel to measure blood sugar non-invasively. This study uses the MAX30100 sensor as a non-invasive measure of blood sugar levels. The Value of blood sugar levels in this instrumentation is displayed on LCD. Tests were carried out on 20 Normal patients and people with diabetes mellitus. Based on the testing and analysis that has been done, this tool still needs to be developed with more data collection, so that the accuracy of checking is getting better.